The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3126/irjms.v4i0.27888
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Financial Performance of Insurance Companies in Nepal

Abstract: This paper aims to examine the effect of corporate governance practice on financial performance of insurance companies in Nepal. The study used board size, number of board meetings, CEO duality, Audit committee are the explanatory variables for corporate governance. Firm size and age of the firms are considered as control variables. The dependent variable performance has been measured using Return on Assets (ROA) and return on equity ROE. The study employed descriptive cum causal relational research design. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…In contrast, ROA and ASize(5) underestimate RE (−6.3918) and relate negatively at 10% significance, thus rejecting Hypothesis 4. This supports the findings of Maharjan (2019), Fadun (2013), andFekadu (2015). This means that below ASize(4), there is no effect on insurance performance, while there is a positive effect on insurance performance when there are four members.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…In contrast, ROA and ASize(5) underestimate RE (−6.3918) and relate negatively at 10% significance, thus rejecting Hypothesis 4. This supports the findings of Maharjan (2019), Fadun (2013), andFekadu (2015). This means that below ASize(4), there is no effect on insurance performance, while there is a positive effect on insurance performance when there are four members.…”
Section: Resultssupporting
confidence: 87%
“…The audit committee's role is to enhance firm value. Maharjan (2019), Fadun (2013), andFekadu (2015) all found a positive relationship between audit committee size and financial performance. In contrast, Datta (2018), Ghabayen (2012), Yemane et al (2015), and found that audit committee size does not affect firm performance.…”
Section: Audit Committee Sizementioning
confidence: 92%
See 2 more Smart Citations
“…For this, a convenient sampling technique has been used for the selection of the sample, and data were analyzed using a multiple linear regression model. Similarly, Maharjan (2019), andGhimire (2020) examine the relationship between corporate governance and the performance of the insurance companies in Nepal with having the effect of corporate governance practice on the financial performance of insurance companies in Nepal.…”
Section: Literature Reviewmentioning
confidence: 99%